O corpo em cena e o corpo fora da cena - Marilia Aparecida Moreira (2013)
This research presents an investigation on the body, delimiting its forms of presentation in subjective urgencies. It explores the theme "The body on the scene and the body out of the scene", focusing on the happenings of the body and considering the incidence of the Real in the present days. This work intends to present contributions to psychological studies, as it addresses the happenings of the body through the bodys outbreak of enjoyment, relating it to the living body and the meaning of life. The theoretical discussion is based on the articulation with the happenings of the body in Antonin Artaud, in its form of presentation: a body that emerges from the Real, revealing a non separation from life, with which he handles as a living body, introducing an important discussion that permeates the reflections of this Masters thesis and the psychoanalytic theoretical foundation about language and culture. On the other hand, as Artaud theorizes about the theater of cruelty, he creates the concept of cruelty as a particular way of dealing with language, verifying, in contrast, on the part of psychoanalysis, the concept of representation. This produces effects on the constitution of a body and the position of the subject in the world. Based on that, this study has established a methodology, which considers two different moments in relation to the construction of the body in Artauds work. One is the body on the scene, that is, the moment that the research with the theater develops, before his hospitalization in Rodez, and the other is the body out of the scene, when he starts the act of writing, dating from this same period. In parallel, on the part of psychoanalysis, we have also delimited these two moments, with focus on Lacans theory: Seminar 10: on anxiety, in which he theorizes on the object, and Seminar 23: on the sinthome, in which the Real and the forms of tying the knot, based on topology, prevail.